1999
DOI: 10.1088/0953-8984/11/37/308
|View full text |Cite
|
Sign up to set email alerts
|

The alternating-current-driven motion of dislocations in a weakly damped Frenkel - Kontorova lattice

Abstract: By means of numerical simulations, we demonstrate that ac field can support stably moving collective nonlinear excitations in the form of dislocations (topological solitons, or kinks) in the Frenkel-Kontorova (FK) lattice with weak friction, which was qualitatively predicted by Bonilla and Malomed [Phys. Rev. B 43, 11539 (1991)]. Direct generation of the moving dislocations turns out to be virtually impossible; however, they can be generated initially in the lattice subject to an auxiliary spatial modulation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
0
12
0
3
Order By: Relevance
“…The results of the simulations are displayed below in the form u = u(γ ac ), using numerically found dependencies V dc (γ ac ) and the relation (8). This way of the presentation of results is the most appropriate one if the objective is to look for dynamical regimes with a nonzero average velocity of the ac-driven kink.…”
Section: A the Model And Computational Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the simulations are displayed below in the form u = u(γ ac ), using numerically found dependencies V dc (γ ac ) and the relation (8). This way of the presentation of results is the most appropriate one if the objective is to look for dynamical regimes with a nonzero average velocity of the ac-driven kink.…”
Section: A the Model And Computational Proceduresmentioning
confidence: 99%
“…Search for such regimes in FK models turned out to be more difficult, but simulations have finally demonstrated that the soliton in the form of a dislocation may be driven with a nonzero mean velocity by the ac force [8].…”
Section: Introductionmentioning
confidence: 99%
“…One such phenomenon is the stable progressive motion of kinks with homogeneous pure AC driving [8][9][10][11]. In a discrete system, kinks experience a periodic potential, namely the Peierls-Nabarro (PN) potential, whose period is the lattice constant of the system, which here is d. Therefore, stable propagation can be maintained only when a kind of mode locking occurs between the external driving and the oscillation of the propagating kinks in the PN potential.…”
Section: Progressive Motion Under Ac Drivementioning
confidence: 99%
“…In a discrete system, kinks experience a periodic potential, namely the Peierls-Nabarro (PN) potential, whose period is the lattice constant of the system, which here is d. Therefore, stable propagation can be maintained only when a kind of mode locking occurs between the external driving and the oscillation of the propagating kinks in the PN potential. Thus, the mean velocity is predicted to be v ¼ m e d Á m=M, where m and M are the super-and subharmonic resonance orders [11]. 3) is considered, the fluxon pair would experience asymmetric PN potential, and the direction of progress would be fixed.…”
Section: Progressive Motion Under Ac Drivementioning
confidence: 99%
“…The ac-driven DSG lattice has two independent sources of non-integrability: the external drive (bias) and the discreteness. Interplay of these two sources has led to a number of interesting effects: mode-locking to the frequency of the external drive [13] and kink mobility [14,15] (including its experimental detection in periodically modulated Josephson junctions [16]), various regimes of the dynamical chaos [13,18], biharmonically driven discrete kink ratchet [17,18] to name a few. However, these studies have been performed mostly in the adiabatic, subband (the driving frequency lies in the gap of the linear spectrum) or resonant (the driving frequency lies in the linear band) cases.…”
Section: Introductionmentioning
confidence: 99%